KEUNIKAN ORNAMEN PADA MASJID TUO KAYU JAO DAN ASPEK-ASPEK YANG MEMPENGARUHI PERWUJUDANNYA - Adetia Anetama; Sangayu Ketut Laksemi Nilotama; Ahadiat Joedawinata (Universitas Trisakti, 2022)
AbstractMasjid Tuo Kayu Jao is one of the oldest mosques in West Sumatra which was built in the 16th century.This mosque now has a simple appearance with ornaments that are not too prominent. However, behindthis simplicity, there is a uniqueness that is interesting to study. Data were taken from field surveys,interviews and literature review. To analyze the uniqueness of the ornaments of the Masjid Tuo KayuJao and the aspects that influence its realization, the theory of “Nine Guiding Elements” is used in theprocess of building and turning one idea into an object by Ahadiyat Joedawinata. Based on the research,it was concluded that there was a meeting of several cultures in the ornaments of the Masjid Tuo KayuJao, namely Minangkabau architecture and Islamic architecture which gave birth to the uniqueness ofthe ornaments. When examined more deeply, this uniqueness was built by various factors so that theMasjid Tuo kayu Jao has a very high value to be used as an example / reference for designing a mosqueat this time. So that the design of mosque ornaments is not only focused on mosques from Arabia orGujarat but can also use the wisdom of archipelago architecture including Minangkabau architecture.Keywords: ornament, unique, Masjid Tuo Kayu JaoAbstrakMasjid Tuo Kayu Jao adalah salah satu masjid tertua di Sumatera Barat yang dibangunpada abad ke-16. Masjid ini sekarang memiliki tampilan yang sederhana dengan ornamenyang tidak terlalu menonjol. Namun, dibalik kesederhanaan itu tersimpan keunikan yangmenarik untuk diteliti. Data diambil dari survei lapangan, wawancara dan kajian literatur.Untuk menganalisa keunikan ornamen Masjid Tuo Kayu Jao dan aspek yang mempengaruhiperwujudannya digunakan teori “Sembilan Unsur Pemandu” dalam proses terbangundan membendanya satu gagasan menjadi objek oleh Ahadiyat Joedawinata. Berdasarkanpenelitian disimpulkan bahwa adanya pertemuan beberapa budaya pada ornamen MasjidTuo Kayu Jao yaitu arsitektur Minangkabau dan arsitektur Islam yang melahirkan keunikanpada ornamennya. Ketika dikaji lebih dalam, keunikan ini ternyata terbangun oleh berbagaimacam faktor sehingga Masjid Tuo Kayu Jao memiliki value yang sangat tinggi untuk dapatdijadikan contoh/acuan perancangan Masjid pada saat ini. Sehingga perancangan ornamenMasjid tidak hanya terpaku pada Masjid dari Arab atau Gujarat tapi juga bisa menggunakankearifan arsitektur nusantara diantaranya arsitektur Minangkabau.Kata kunci: ornamen, unik, Masjid Tuo Kayu Jao